2017
DOI: 10.1111/mec.13994
|View full text |Cite
|
Sign up to set email alerts
|

Endemic species may have complex histories: within‐refugium phylogeography of an endangered Iberian vole

Abstract: Glacial refugia protected and promoted biodiversity during the Pleistocene, not only at a broader scale, but also for many endemics that contracted and expanded their ranges within refugial areas. Understanding the evolutionary history of refugial endemics is especially important in the case of endangered species to recognize the origins of their genetic structure and thus produce better informed conservation practices. The Iberian Peninsula is an important European glacial refugium, rich in endemics of conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 85 publications
1
45
3
Order By: Relevance
“…Aridity does not have a constraining role in the distribution of this rodent (Table ) because distribution changes from MHPC to APC and from APC to AC reveal a continuous shift from low aridity regions (Pirenaic‐Occitanan) to others of greater aridity (Betic, Montiberican and Luso‐Carpetanian; see aridity map in Figure S3 in Appendix S3 and current versus Mid‐Holocene climate comparison in Appendix S4). This conclusion is corroborated by phylogenetic data of the species (Barbosa et al., ; Figure ), which do not show any evidence of demographic reduction linked to the 5.3 ka BP (Atlantic‐Subboreal transition) climatic crisis but, instead, a constant population increase throughout the Holocene with a more sudden decline at 1.5–2.0 ka. Furthermore, a recent archaeological review questions the ecologic effects of the 5.3 ka BP climatic crisis in the Iberian Peninsula, indicating that this degradation may not be related to an increase in aridity but to a geographical redistribution of human populations and changes in their systems of exploitation of resources (Almagro‐Gorbea, ).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Aridity does not have a constraining role in the distribution of this rodent (Table ) because distribution changes from MHPC to APC and from APC to AC reveal a continuous shift from low aridity regions (Pirenaic‐Occitanan) to others of greater aridity (Betic, Montiberican and Luso‐Carpetanian; see aridity map in Figure S3 in Appendix S3 and current versus Mid‐Holocene climate comparison in Appendix S4). This conclusion is corroborated by phylogenetic data of the species (Barbosa et al., ; Figure ), which do not show any evidence of demographic reduction linked to the 5.3 ka BP (Atlantic‐Subboreal transition) climatic crisis but, instead, a constant population increase throughout the Holocene with a more sudden decline at 1.5–2.0 ka. Furthermore, a recent archaeological review questions the ecologic effects of the 5.3 ka BP climatic crisis in the Iberian Peninsula, indicating that this degradation may not be related to an increase in aridity but to a geographical redistribution of human populations and changes in their systems of exploitation of resources (Almagro‐Gorbea, ).…”
Section: Discussionsupporting
confidence: 58%
“…Overall, our study suggests that, without human pressure, the expansion of M. cabrerae 's distribution area that started after the LGM could continue (and intensify) during the Holocene, associated with a concomitant increase in population size (Barbosa et al., ) . We note that Araújo, Guilhaumon, Rodrogues Neto, Pozo Ortego, and Gómez Calmaestra () and Mestre et al.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In this context, the protection of these sparsely distributed habitat patches that appear and disappear through both space and time is likely to reduce the susceptibility of more isolated metapopulations to extinction and prevent a generalized loss of genetic diversity (Frankham et al., ; Mills, ). Previous phylogeographic studies identified two main mitochondrial lineages that likely diverged during and after the last glacial maximum and that are now in secondary contact (Barbosa et al., ). However, the observed nuclear differentiation (based on the analysis of a few autosomal and sex‐linked loci) was very low and inadequate to define CUs .…”
Section: Introductionmentioning
confidence: 99%